OPTIMIZATION OF TEACHERS' PEDAGOGICAL COMPETENCE THROUGH COACHING AT KASIH IBU SLB PEKANBARU - Yasni Yasni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper is based on the teachers’ low pedagogical competence at SLB Kasih Ibu Pekanbaru. It is found from 1) there are still teachers who are unable to develop the syllabus, 2) there are still teachers who have not been able to manage the class properly, 3) there are still teachers who have not been able to interact and communicate well with students, 4) there are still teachers who have not been able to allocate time properly, 5) there are still teachers who do not motivate students to involve themselves actively in the teaching and learning process, and 6) there are still teachers who use learning media and deliver teaching material by only applying lecture or conventional methods. The research uses a School Action Research design by Kurt Lewin. The main concept of PTS according to Kurt Lewin consists of four components. The population of the research involved 13 all teachers at SLB Kasih Ibu Pekanbaru. Based on the description of data processing and discussion, the teacher's pedagogical competence in cycle I was 66% in the good category and in cycle II it increased to 88% in the good category. It means that coaching activities can improve the teachers’ pedagogical competence at SLB Kasih Ibu Pekanbaru, which is successful.